ChemInform Abstract: Efficient Asymmetric Transfer Hydrogenation of N‐Sulfonylimines on Water. Issue 48 (26th November 2013) - Wang, Lei; Zhou, Qi; Qu, Chuanhua; Wang, Qiwei; Cun, Linfeng; Zhu, Jin; Deng, Jingen
Abstract The asymmetric transfer hydrogenation of a range of N‐sulfonyl ketimines is achieved with sodium formate and (R, R)‐Ts‐DPEN as the chiral ligand.